Peace and Order Situation Amidst the COVID-19 Pandemic at Barangay 188 Tala, Caloocan City: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
According to Albert Einstein, peace is not merely the absence of war but the presence of justice, law, order, and government. Indeed, a certain place, barangay, city, or country should have a government that properly implements its fundamental laws, provisions, and regulations for peace and order to be achieved. Thomas Jefferson, likewise, believes that the masses, or the people themselves, need to be educated on the importance of peace and order for the people to preserve them. Both the government and the masses are responsible for maintaining peace and order to live a harmonious life, but how is this possible if the world is in a pandemic, stirring fear and unrest amongst many due to its fatal effect?Due to the challenges encountered by the barangay, the researchers aim to determine the situation of peace and order amidst the COVID-19 pandemic at Barangay 188, Tala, Caloocan City, to assess whether the officials can implement the standard protocols as stated in the IATF guidelines and whether the residents and/or non-residents can follow these guidelines to ensure that peace and order are observed despite the current pandemic situation. The study will focus on determining whether checkpoints are indeed set in strategic places within the barangay; whether curfew ordinances and other monitoring and evaluations on activities in and outside the residences are observed and followed; and whether the quarantine pass directive is constant and religiously checked and monitor. In assessing these activities, the study will identify whether the barangay ensures peace and order are implemented accordingly, and it will be a basis for future studies or will be mirrored by other barangay with the same conditions.The researchers aim to employ descriptive methods to describe the nature of the situation as it exists in the real world and explore the cause of the particular phenomenon. The descriptive and inferential methods were used in gathering information for the researchers to know the Preservation of Peace and Order Situation amidst the COVID-19 Pandemic at Barangay 188, Tala, Caloocan City. The researchers utilised a questionnaire as their measuring instrument in gathering and collecting data. The collected data was assessed and validated by the researchers.